Pengaruh Anggaran Berbasis Kinerja, Budaya Organisasi, dan Disiplin Pegawai terhadap Kinerja Aparatur Pemerintah Dinas Sosial Kabupaten Aceh Barat - Enjelina; Marlina, Lilis; Mahdani, Said; Fatmayanti; Sartika, Dewi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the influence of performance-based budgeting, organizational culture, and employee discipline on the performance of government apparatus at the Social Service Office of West Aceh Regency. The research employed a quantitative approach using a survey method and questionnaire data collection from 42 respondents. The results of multiple linear regression analysis show that organizational culture and employee discipline have a positive and significant effect on apparatus performance, with t-values of 4.535 (p = 0.000) and 2.217 (p = 0.033), respectively. In contrast, performance-based budgeting does not have a significant effect (t = 0.239; p = 0.813). Simultaneously, all three independent variables significantly affect the performance of government apparatus (F = 19.502; p < 0.001), with an adjusted R² value of 0.575. These findings indicate that organizational culture and discipline are the main determinants of government performance at the Social Service Office of West Aceh Regency.